Preliminary results of a fertilization-irrigation experiment in a Quercus ilex L. forest in relation to leaves and twigs characteristics (Plant Ecology, 1992)
A multifactorial ANOVA experiment was designed for a Quercus ilex forest in the Prades mountains in Tarragona (NE Spain). The purpose of this study was to clarify the relative importance of water, ni- trogen and phosphorus as factors controlling primary production. Eight plots comprising all possible combinations of the three factors (including a control) were laid out in three replicate blocks. Fertilizers were applied to the appropriate treatments in March 1989 with a dosage of 125 kg of P/ha and 250 kg N/ha. Irrigation was applied with a rate of 20 mm per week during the warm season. To evaluate the effects on canopy structure we measured specific leaf weight (rag/cruZ), average leaf weight (rag), average twig height and average twig length. These variables were selected as they are the most likely to manifest changes over short time periods following changes in environmental conditions. The values of these parameters before initial treatments (autumn 1988) and after treatments (summer 1990) were analyzed. The results obtained show that water and nitrogen have a greater effect than phosphorus on tree canopy structure, at least during initial development.